ESTIMASI WAKTU ULANG DAN DIMENSI PATAHAN PENYEBAB GEMPABUMI PADANG, SUMATERA BARAT 6 APRIL 2010 - Ratni Sirait (EINSTEIN (e-Journal), 2020)
The data used in this study are earthquake data with a magnitude of 7.8 MW, taken from the USGS (United State Geological Service) at coordinates 2.383 ° N 97.048 ° E which is right above the Sunda megathrust zone. This study aims to determine the estimated return time and fault dimensions that caused the tectonic earthquake that occurred in Padang, West Sumatra April 6, 2010. This research was conducted using a mathematical method that refers to the Weels and Coppersmith equation (1994) as well as equations from Kanamori and Anderson ( 1975). Based on the magnitude of the earthquake, which is 7.8 MW with a main slip value of 1.2 meters, the estimated return time of this earthquake is 24, 50 years, as well as the fault dimensions with a fault length of 4.66 meters, a fault width of 6.76 meters, and an area of fault 31.48 meters